2016
DOI: 10.5194/amt-9-3131-2016
|View full text |Cite
|
Sign up to set email alerts
|

PHIPS–HALO: the airborne Particle Habit Imaging and Polar Scattering probe – Part 1: Design and operation

Abstract: Abstract. The number and shape of ice crystals present in mixed-phase and ice clouds influence the radiation properties, precipitation occurrence and lifetime of these clouds. Since clouds play a major role in the climate system, influencing the energy budget by scattering sunlight and absorbing heat radiation from the earth, it is necessary to investigate the optical and microphysical properties of cloud particles particularly in situ. The relationship between the microphysics and the single scattering proper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 32 publications
0
50
0
Order By: Relevance
“…Since the liquid water content that freezes does not vary with updraft strength, the freezing of more numerous droplets in the faster updrafts simply produces smaller ice particles. This is clearly shown by Ackerman et al (2015), in which ice particle mass distributions in homogeneous freezing for stronger updrafts produce substantially smaller ice particles. Schnaiter et al (2016) further showed that high ice particle growth rates also enhance the formation of small-scale complexity, such as ice particle surface roughness.…”
Section: The Cloud Chambermentioning
confidence: 80%
See 1 more Smart Citation
“…Since the liquid water content that freezes does not vary with updraft strength, the freezing of more numerous droplets in the faster updrafts simply produces smaller ice particles. This is clearly shown by Ackerman et al (2015), in which ice particle mass distributions in homogeneous freezing for stronger updrafts produce substantially smaller ice particles. Schnaiter et al (2016) further showed that high ice particle growth rates also enhance the formation of small-scale complexity, such as ice particle surface roughness.…”
Section: The Cloud Chambermentioning
confidence: 80%
“…Wendisch and Brenguier (2013) compiled a comprehensive list covering 48 different instruments, many of which are historical, but recently there have been several new developments, e.g. Abdelmonem et al (2016) and Baumgardner et al (2014Baumgardner et al ( , 2017. Many of the current techniques, however, are technological improvements on previous instruments originally developed and flown in the 1970s.…”
Section: Introductionmentioning
confidence: 99%
“…The Particle Habit Imaging and Polar Scattering probe (Abdelmonem et al, 2016) data were used to discriminate ice particles and droplets based on angular light scattering measurements (Schnaiter et al, 2018). The appearance of liquid droplets in clouds was defined when the LWC is greater than 0.005 g m −3 in a previous study by Baumgardner and Rodi (1989).…”
Section: Methodsmentioning
confidence: 99%
“…(e.g. Macke et al, 1996;Yang and Liou, 1998;Baran et al, 2001; Baran and Francis, 2004;Sun et al, 2004;Yang et al, 2008;Baum et al, 2010;Platnick et al, 2017). Later, it was found that ice crystal parameterizations implementing roughened surfaces represent the measured optical properties, especially the polarization effects of atmospheric ice clouds, more accurately than parameterizations based on a mixture of pristine ice crystals (Baran and Labonnote, 2006;Um and McFarquhar, 2007;Jourdan et al, 2010;Liu et al, 2014b;Yi et al, 2016;Tang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%